Inflammatory and regenerative processes in bioresorbable synthetic pulmonary valves up to two years in sheep–Spatiotemporal insights augmented by Raman microspectroscopy. (November 2021) - De Kort, B.J.; Marzi, J.; Brauchle, E.M.; Lichauco, A.M.; Bauer, H.S.; Serrero, A.; Dekker, S.; Cox, M.A.J.; Schoen, F.J.; Schenke-Layland, K.; Bouten, C.V.C.; Smits, A.I.P.M.
Abstract: In situ heart valve tissue engineering is an emerging approach in which resorbable, off-the-shelf available scaffolds are used to induce endogenous heart valve restoration. Such scaffolds are designed to recruit endogenous cells in vivo, which subsequently resorb polymer and produce and remodel new valvular tissue in situ . Recently, preclinical studies using electrospun supramolecular elastomeric valvular grafts have shown that this approach enables in situ regeneration of pulmonary valves with long-term functionality in vivo . However, the evolution and mechanisms of inflammation, polymer absorption and tissue regeneration are largely unknown, and adverse valve remodeling and intra- and inter-valvular variability have been reported. Therefore, the goal of the present study was to gain a mechanistic understanding of the in vivo regenerative processes by combining routine histology and immunohistochemistry, using a comprehensive sheep-specific antibody panel, with Raman microspectroscopy for the spatiotemporal analysis of in situ tissue-engineered pulmonary valves with follow-up to 24 months from a previous preclinical study in sheep. The analyses revealed a strong spatial heterogeneity in the influx of inflammatory cells, graft resorption, and foreign body giant cells. Collagen maturation occurred predominantly between 6 and 12 months after implantation, which was accompanied by a progressive switch to a more quiescent phenotype of infiltrating cells with properties of valvular interstitial cells. Variability among specimens in the extent of tissue remodeling was observed for follow-up times after 6 months. Taken together, these findings advance the understanding of key events and mechanisms in material-driven in situ heart valve tissue engineering. Statement of significance: This study describes for the first time the long-term in vivo inflammatory and regenerative processes that underly in situ heart valve tissue engineering using resorbable synthetic scaffolds. Using a unique combinatorial analysis of immunohistochemistry and Raman microspectroscopy, important spatiotemporal variability in graft resorption and tissue formation was pinpointed in in situ tissue-engineered heart valves, with a follow-up time of up to 24 months in sheep. This variability was correlated to heterogenous regional cellular repopulation, most likely instigated by region-specific differences in surrounding tissue and hemodynamics. The findings of this research contribute to the mechanistic understanding of in situ tissue engineering using resorbable synthetics, which is necessary to enable rational design of improved grafts, and ensure safe and robust clinical translation. Graphical abstract: Image, graphical abstract